2016
DOI: 10.20546/ijcrar.2016.401.007
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Cardiac Cost of Two Age Groups of Brick Carriers During Summer in Different Unorganized Brick making Sector in West Bengal, India

Abstract: In brick making industry, brick carrying activity requires extreme physical efforts and imposes additional load on cardiovascular system of the workers in hot environment. Lack of data about age associated alteration of cardiac cost among the brick carriers impinged us for this study. The purpose of this study was to assess the cardiac cost of two age groups of brick carriers in summer seasons. 156 brick carriers, having minimum one years experiences, were divided into two groups i.e., younger carriers and old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…A similar study was conducted to assess the cardiac costs of male brick kiln workers of two different age groups [11], and it was observed that mean (SD) Maximum Heart Rate (HR max) of the younger group (18-39 years) was 142.55 (5.63) beats/min at higher WBGT. But this study showed that mean peak heart rate of the MMH workers was 147.0 (11.44) beats/min at lower WBGT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar study was conducted to assess the cardiac costs of male brick kiln workers of two different age groups [11], and it was observed that mean (SD) Maximum Heart Rate (HR max) of the younger group (18-39 years) was 142.55 (5.63) beats/min at higher WBGT. But this study showed that mean peak heart rate of the MMH workers was 147.0 (11.44) beats/min at lower WBGT.…”
Section: Discussionmentioning
confidence: 99%
“…Heavy load carriage, awkward postures for a prolonged duration, environmental stress, lack of usage of personal protective equipment are cumulatively affecting the health status of workers. Angular deviation of joint angles from neutral posture, continuous and speedy work pattern, and heavy load carriage can exert the cardiovascular load on the workers, and it enhances with increased environmental temperature and humidity [11,12].…”
Section: Introductionmentioning
confidence: 99%